Trafficking in human beings as a specific form of women's migration - Mrvić-Petrović Nataša (Temida)
The author is analyzing trafficking in human beings as a specific form of women's (illegal) migration. The author is presenting detailed analysis of the international standards and recent activities of different international organizations (UN, Council of Europe, European Community, OSCE), concerning prevention of trafficking in human beings, regulation of foreign migrants' status and protection of victims of trafficking. Starting from the analysis of international documents and national legislations dealing with migration and prostitution, the author is proposing changes of existing domestic laws concerning movement and residence of foreigners. The aim of such changes is to harmonize our legislation with international standards and obligations accepted by signing the Palermo Convention.